Researching digitalized work arrangements: A Laws of Form perspective. Issue 2 (June 2022) - Rehm, Sven-V.; Goel, Lakshmi; Junglas, Iris
Abstract: Advances in digitalization have changed our apprehension of technology from discrete devices and application software as bounded artifacts, to dynamically evolving social-material entanglements in Digitalized Work Arrangements (DWA). This development makes studying DWAs increasingly difficult and challenges us to advance our methods that define how we can study, observe, and conceptualize DWAs. In this essay, we draw on the mathematical-logical formalism of the Laws of Form (LoF) (Spencer-Brown, 1969 ) to analyze how six illustrative IS studies conceptualize the social and the material to arrive at distinct perspectives on DWAs. Our analysis reveals three archetypes that capture these studies' conceptualizations and that inform a discussion of how IS research can extend qualitative methods beyond those six works. We offer two contributions. First, we provide novel insights and explanations to key conceptualizations in the study of DWAs. Second, we present the LoF as a pre-ontological and pre-theoretical formalism that enables commensurability of methods and development of novel qualitative empirical methods. Specifically, we demonstrate how the formalism helps articulating the distinctions we draw to refine our object of study and to critically examine and reconstruct other researchers' reasoning. Highlights: Studying DWAs requires problematization of their dynamics and emergent nature. The LoF enables formalizing conceptualizations of social-material entanglements in DWAs. LoF is a pre-ontological, pre-theoretical formalism that enables development and critique of conceptualizations and methods.